Analisis Resepsi Pemain dalam Video Game “Among Us” - Ricky Widyananda Putra; Jeanie Annissa (Neolectura, 2022)
Game is an entertainment facility that contains games using electronic devices which involve players who make decisions through control of game objects for certain purposes, known as users. The game growth industry has developed especially in a variety of types of games which include Maze Game, Board Game, Card Game, Battle Card Game, Quiz Game, Puzzle Game, Shooting Game, First Person Shooting (FPS), Side Scrolling Game, Fighting Game , Racing Game, Simulation, Strategy Game, Role Playing Game (RPG), Adventures Game, Sport Game, and Edutainment Game. In Indonesia itself, there are a variety of online games that have sprung up, among the many types of online games that are currently being talked about is the